A new species of Cyrtocarpa (Anacardiaceae) from Mexico - Fonseca, Rosa María (Instituto de Ecología, A.C., 2005)
Cyrtocarpa kruseana, from the Mexican states of Chiapas, Guerrero, Jalisco and Nayarit, is described as new and illustrated. This species is similar to Cyrtocarpa velutinifolia from South America on account of the inflorecense size and position, and it differs from the Mexican species especially in the size of the fruit, size and position of the inflorescence, and phenology.